The Influence of Organizational Culture and Organizational Climate on Work Productivity With Job Satisfaction as an Intervening Variable at PT. Usaha Muda Sejahtera Pasaman Timur - Fitri Suherini; John Veri (Sean Institute, 2025)
This study aims to examine the influence of organizational culture and organizational climate on work productivity with job satisfaction as an intervening variable at PT. Usaha Muda Sejahtera Pasaman Timur. The data collection method was through a survey and distributing questionnaires, with a sample of 74 respondents. The analytical method used was path analysis using smartpls. The research results show a significant influence of organizational culture on job satisfaction. There is a significant influence of organizational climate on job satisfaction. There is a significant influence of organizational culture on work productivity. There is an insignificant influence of organizational climate on work productivity. There is an insignificant influence of job satisfaction on work productivity. There is an insignificant influence of organizational culture on work productivity through job satisfaction. There is an insignificant influence of organizational climate on work productivity through job satisfaction.